Beyond acacia: exploring the unique rheological properties and flowability of Boswellia Sacra gum for industrial use - Asmaa Al-Hamayda; Mutamed Ayyash; Basim Abu-Jdayil (Applied Food Research, 2025)
This study characterizes a previously unexplored Omani gum (OG) derived from Boswellia sacra that has potential as a versatile hydrocolloid in food and pharmaceutical applications. Comprehensive analyses of bulk powder characteristics and rheological behavior were performed, with gum Arabic (GA) included as a reference for comparison. OG solutions at five concentrations (5 %–40 %) were evaluated and compared to GA solutions at the same concentrations. OG achieved a Hausner ratio of 1.48 and Carr index of 32.5 %, while GA achieved corresponding values of 1.34 and 25.5 %, respectively. Furthermore, OG exhibited water- and oil-holding capacities of 1.714 and 0.497 g/g, respectively, while GA exhibited corresponding values of 20.588 g/g and 1.80 g/g. Rheological characterization included flow curve analysis, amplitude sweep, frequency sweep, thixotropy sweep, and temperature sweep to assess the flow behavior, viscoelastic properties, structural recovery, and thermal stability of the gum solutions. OG exhibited predominantly shear-thinning behavior across all concentrations. OG displayed a predominantly shear-thinning behavior across all tested concentrations. Rheological data fitted well to the Power Law, Bingham, and Casson models, with the Power Law model offering the best fit, as indicated by superior R² and lower RMSE values. According to the Power Law, the flow behavior index (n) decreased from 0.94 to 0.88 with increasing OG concentration. Temperature sweep results indicated that OG maintained its structure over a wide thermal range, with minimal loss of viscoelastic properties. Temperature dependency of viscosity was further analyzed using the Arrhenius model, yielding activation energy values between 9.76 and 24.02 kJ/mol, consistent with values reported for other plant-derived gums. These results demonstrate the potential of OG as a novel and competitive alternative to widely used gums, making it a promising candidate for diverse applications.